On the way to Ithaka[1]: Commemorating the 50th Anniversary of the Publication of Karl E. Weick's The Social Psychology of Organizing. (10th September 2020) - Tsoukas, Haridimos; Patriotta, Gerardo; Sutcliffe, Kathleen M.; Maitlis, Sally
Abstract: Karl E. Weick's The Social Psychology of Organizing has been one of the most influential books in organization studies, providing the theoretical underpinnings of several research programs. Importantly, the book is widely credited with initiating the process turn in the field, leading to the 'gerundizing' of management and organization studies: the persistent effort to understand organizational phenomena as ongoing accomplishments. The emphasis of the book on organizing (rather than on organizations) and its links with sensemaking have made it the most influential treatise on organizational epistemology. In this introduction, we review Weick's magnum opus, underline and assess its key themes, and suggest ways in which several of them may be taken forward.